Integrating value-focused thinking and FITradeoff to support information technology outsourcing decisions. Issue 11 (6th July 2020) - Poleto, Thiago; Clemente, Thárcylla Rebecca Negreiros; de Gusmão, Ana Paula Henriques; Silva, Maisa Mendonça; Costa, Ana Paula Cabral Seixas
Abstract : Purpose: The information technology (IT) outsourcing (ITO) decision is a key issue in strategic and operational management and is considered a main critical factor influencing successful organizational performance and technology assessment. The purpose of this paper is to propose a framework combining value-focused thinking (VFT) methodology and the FITradeoff method to support decisions regarding ITO. Design/methodology/approach: This study answers the following questions: How to identify, in a structured way, the objectives that should be considered in an ITO decision process in a changing environment? How to identify new IT services to be outsourced from the established objectives? The VFT method is recommended in this case to structure and model the problem. Moreover, the FITradeoff multicriteria method was considered in this study to support the evaluation and prioritization of IT services in an ITO decision Findings: The framework provides promising results for ITO decisions. This study revealed that a lack of strategic and fundamental objectives is a critical issue in making ITO decisions. Although the VFT methodology is subjective in nature, it promotes a better understanding of goals and values, and FITradeoff allows the decision-maker to make comparisons of consequences based on his/her preferences. Research limitations/implications: The recommendations of the study are restricted to the case study and cannot be generalized. In addition, applying the method requires attention in determining the criteria used for outsourcing IT. Practical implications: The strategic analysis of ITO provides a holistic view of the current situation since (i) the VFT methodology enables the IT manager to generate new alternatives to assist future decisions and (ii) FITradeoff has been demonstrated as a suitable option to evaluate ITO decisions. Originality/value: To the best of our knowledge, this is the first paper to utilize a problem structuring method (VFT) to identify criteria and alternatives based on the organizational values and objectives. This is integrated with a multicriteria method that uses partial information and may consequently lead to fewer inconsistencies (FITradeoff) in the context of ITO.